Adaptive fractional Fourier domain filtering - Durak, L.; Aldirmaz, S. (ELSEVIER SCIENCE BV, 2010)
A novel adaptive filtering scheme based on fractional Fourier transform (FrFT) is introduced and characterized. As a generalization of the ordinary Fourier transform, FrFT is a powerful analysis tool to describe signals with chirp-type components. We show that in case of linear frequency modulated (LFM) signals fractional Fourier domain adaptive filtering schemes provide less error and faster convergence. The adaptation algorithm is employed in an active noise control system application with various LFM signals and a real multi-component signal. Simulation results present that the adaptation performance in FrFT-domain adaptive filtering is superior compared to time-domain adaptation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Active noise control; Adaptive filters; Fractional Fourier domains; Fractional Fourier transform; Least mean squares algorithms; ACTIVE NOISE-CONTROL; NEURAL-NETWORK; TRANSFORM; IMPLEMENTATION; CANCELLATION; SPEECH; SYSTEM; Engineering